Design And Development Of Auto-Steel Draw Forming Test Device - Sulaiman, Saiful Naim; Abu Shah, Ismail; Halim, Mohd Faizal; Tamin, Mohd Nasir (Asian Research Publishing Network (ARPN), 2016)
This work is concerned with the design and development of draw forming test device with double action draw forming mechanism.This device is designed to operate on universal testing machine (UTM).The dual phase auto-steel about 1.2 mm thick is used as deformable blank.The double action mechanism is generated by an external hydraulic system to equally apply the blank holder force (BHF).Hence,the punch force is driven by UTM’s hydraulic system.The design load and die displacement is initially predicted by FE simulation at maximum load of 123kN and 14 mm displacement respectively.Draw forming result shows the fracture is recorded at 108 kN of punch force and 9.5 mm of displacement depth.